The Effect of Post‐Treatment Combined Lifestyle Interventions on Quality of Life in Colorectal Cancer Patients - A Systematic Review - Anke H. C. Gielen; Britt J. M. Thomassen; Tim J. Bult; Jarno Melenhorst; Merel L. Kimman; Stephanie O. Breukink (Wiley, 2024)
ABSTRACT Background Colorectal cancer is identified as a lifestyle‐related type of cancer. There is an increasing emphasis on lifestyle interventions targeting pivotal lifestyle factors such as excess weight, cigarette smoking, alcohol consumption, poor diet and physical inactivity as primary and tertiary prevention. Furthermore, modifying these lifestyle factors has the potential to improve quality of life for cancer patients. We aim to identify, appraise and synthesise the available evidence regarding the effect of combined lifestyle interventions on quality of life in colorectal cancer survivors. Methods Pubmed, Ovid Embase and the Cochrane Library were searched for studies reporting on quality of life in post‐treatment colorectal cancer patients. The systematic literature search was performed according to the Preferred Reporting Items for systematic reviews and meta‐analysis (PRISMA) guidelines. Results Five articles reporting on 719 individual patients were included. Two studies reported significantly better results in (cancer‐specific) quality‐of‐life questionnaires for patients after combined lifestyle interventions. Conclusion We conclude that there is some evidence that combined lifestyle interventions could have beneficial effects on the quality of life of colorectal cancer survivors. Future randomised controlled trials reporting on quality of life of combined lifestyle interventions in colorectal cancer survivors are warranted.